Spatial and temporal patterns of surface–atmosphere energy exchange in a dense urban environment using scintillometry. (7th February 2017) - Crawford, B.; Grimmond, C. S. B.; Ward, H. C.; Morrison, W.; Kotthaus, S.
Abstract : Spatially integrated measurements of the surface energy balance (SEB) are needed in urban areas to evaluate urban climate models and satellite observations. Scintillometers allow observations of sensible heat flux ( Q H ) over much larger areas than techniques such as eddy covariance (EC), however methods are needed to partition between remaining unmeasured SEB terms. This is the first study to use observed spatial and temporal patterns of Q H from a scintillometer network to constrain estimates of remaining SEB terms in a dense, heterogeneous urban environment. Results show that Q H dominates the surface energy balance in central London throughout the year, with expected diurnal courses and seasonal trends in Q H magnitude related to solar radiation input. Measurements also reveal a clear anthropogenic component of Q H with winter (summer) weekday Q H values 11.7% (5.1%) higher than weekends. Spatially, Q H magnitude is correlated with vegetation and building landcover fraction in the measurement source areas. Spatial analysis provides additional evidence of anthropogenic influence with highest weekday/weekend ratios (1.55) from the City of London. Spatial differences are used to estimate horizontal advection and a novel method to estimate monthly latent heat flux is developed based on observed landcover and wet–dry surface variations in normalized Q H . Annual anthropogenic heat emissions are estimated to be 46.3 W m −2 using an energy balance residual approach. The methods presented here have potential to significantly enhance understanding of urban areas, particularly in areas with tall buildings where there are few observational data.